A Case of Oropharyngeal Bullous Pemphigoid Presenting with Haemoptysis - C. M. Lee; H. K. Leadbetter; J. M. Fishman (Case Reports in Otolaryngology)
Objective. Bullous pemphigoid is well known for its cutaneous features; however in rare cases it may present with mucosal involvement. We report a case of bullous pemphigoid presenting with haemoptysis, initially presenting to the Ear, Nose and Throat Department for investigation. Methods. An 87-year-old lady was admitted with haemoptysis. She also complained of a spreading, pruritic, bullous rash, which first began three weeks previously. Initial investigations, which included nasendoscopy, revealed a normal nasal mucosa and a normal postnasal space. A large deroofed blister was observed on the soft palate. The presenting symptoms and signs raised the suspicion of an immunobullous disease including bullous pemphigoid. Conclusion. Bullous pemphigoid (BP) is a subepidermal immunobullous disease that typically manifests in elderly patient populations. Although rare, BP can present in a mucocutaneous fashion akin to its more aggressive variant, mucous membrane pemphigoid (MMP). Differentiation of the two is based on clinical grounds, with the prevailing feature for the latter being the predominance of mucosal involvement, which may be extensive. The mainstay of treatment for bullous pemphigoid is steroid therapy, which may be administered both topically and systemically. A deeper understanding into the pathophysiology of the various immunobullous diseases may assist in our understanding of how the various disease entities manifest themselves.